Performance of fly ash based geopolymer concrete with partial replacement of fine aggregate by steel mill slag. (2022) - Premkumar, R.; Chokkalingam, Ramesh Babu; Rajesh, S.
Abstract: Many of these wastes can be recycled or reused in recent years. As a building material in concrete, some of these can reduce landfill costs and protect the environment from negative effects. The recycling and use in the construction sector of industrial byproducts complement sustainable technology and development considerably. Geopolymer is an environmentally sustainable replacement for the standard Portland cement binders, a new generation of binding material. As an alkaline activator, sodium hydroxide solution with 12 mol and sodium silicate was used. The alkaline liquid to fly ash ratio in all the mixes is 0.4. Consider the oven temperature of 70 °C for 48 h and the curing conditions in the environment. The compressive strength, water absorption, and density of the concrete were all measured on each specimen. According to the tests, the compressive strength increases as the amount of steel mill slag increases. Steel mill slag is the alternative fine particle in geopolymer concrete.